2010
DOI: 10.1128/jvi.00416-10
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol Ester-Induced Human Cytomegalovirus Major Immediate-Early (MIE) Enhancer Activation through PKC-Delta, CREB, and NF-κB Desilences MIE Gene Expression in Quiescently Infected Human Pluripotent NTera2 Cells

Abstract: Novel strategies to mitigate the disease burden resulting from human cytomegalovirus (CMV) (HCMV) reactivation are needed. Knowledge about the ways in which HCMV major immediate-early (MIE) gene expression breaks silence from latency to start the viral replicative cycle has the potential to inform the development of new therapies to preempt viral replication. However, the molecular mechanisms that regulate the switch from HCMV MIE gene silence to activation are poorly understood.The expression of viral MIE gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 61 publications
(108 reference statements)
4
43
0
Order By: Relevance
“…Especially for the HCMV latency study, the clinical isolates commonly entered and exited latency in hematopoietic cells, but AD169 failed to become latent in CD34 + cells (Goodrum et al, 2007) and CD14 + cells (Hargett and Shenk, 2010). Whereas Towne has been shown to successfully establish latency in the NT2 cells (Gonczol et al, 1984; Liu et al, 2010) and GM-Ps (Kondo et al, 1994), as well as in T98G cells as demonstrated in the present study. The different abilities to establish latency possibly contributed by the genetic differences among different strains.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Especially for the HCMV latency study, the clinical isolates commonly entered and exited latency in hematopoietic cells, but AD169 failed to become latent in CD34 + cells (Goodrum et al, 2007) and CD14 + cells (Hargett and Shenk, 2010). Whereas Towne has been shown to successfully establish latency in the NT2 cells (Gonczol et al, 1984; Liu et al, 2010) and GM-Ps (Kondo et al, 1994), as well as in T98G cells as demonstrated in the present study. The different abilities to establish latency possibly contributed by the genetic differences among different strains.…”
Section: Discussionsupporting
confidence: 72%
“…Epidermal growth factor receptor (EGFR), its downstream phosphatidylinositol-3-kinase (PI(3) K) Kim et al, 2016), and HCMV-encoded miR-UL148D mediated immediate early response gene 5 (IER5)-cell division cycle 25B (CDC25B) (Pan et al, 2016) promote HCMV latency in CD34 + cells. PKA-CREB-TORC2 signaling cascade (Yuan et al, 2009), PKC mediated cellular CREB and NF-κB (Liu et al, 2010), and mitogen and stress activated kinases coupled with CREB (Kew et al, 2014) have been reported to activate IE gene expression from latency. The cellular signaling pathway involved in the HCMV reactivation is dependent on the stimuli and cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Keller et al (38) showed that while abrogation of the enhancer ATF/CREB elements in the HCMV MIEP failed to alter viral replication in proliferating cells, a minimal negative effect was observed after stimulation of the cyclic AMP (cAMP)/protein kinase A (7,16,27). In this line, in a recent study, desilencing of the HCMV MIE genes during HCMV quiescence in NT-2 cells has been reported to be impaired by abrogation of the NF-B and CREB sites (46). Our results, however, indicate that HCMV growth is not influenced by the absence of the enhancer AP-1 elements under starvation conditions or strong activation of the corresponding signaling pathway by TPA.…”
Section: Discussionmentioning
confidence: 57%
“…Notably, HCMVs with the complete enhancer region eliminated fail to replicate in cultured fibroblasts (27), demonstrating a crucial genetic role for this regulatory region. The contribution of a number of binding sites for cellular transcription factors in the enhancer has been extensively assessed in cell reporter assays and shown to affect promoter function, and more recently in specific cases, the roles of particular sites have been examined in the context of infection (7,16,17,27,32,37,38,43,46,55). However, due to the strict species specificity associated with HCMV, the impact of disrupting enhancer elements in a natural infection cannot be approached.…”
mentioning
confidence: 99%
“…The MIEP contains binding sites for a number of transcription factors that are responsive to PMA such as NF-κB and CREB (Liu et al, 2010), but it is unknown if the MIEP would be directly responsive to 1,25-dihydroxyvitamin D3. We cloned the HMCV IE promoter from the HCMV-FIX strain into the luciferase reporter pGL3 so that we could test whether 1,25-dihydroxyvitamin D3, like PMA would be able to directly stimulate the MIEP-luciferase reporter gene.…”
Section: Resultsmentioning
confidence: 99%